Crosslinked copolymer, polymer membrane comprising same, and anion exchange membrane comprising polymer membrane

By crosslinking copolymers of poly(styrene-b-ethylene-co-butene-b-styrene) and poly(aryl piperidinium), the anion exchange membrane in AEMFC was solved under high temperature and high pH conditions. The problem of insufficient mechanical properties and chemical stability has achieved the improvement of high ionic conductivity and mechanical properties, and is suitable for fuel cells.

CN119256025APending Publication Date: 2025-01-03HANWHA SOLUTIONS CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380042710.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-28
Filing Date
2023-03-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing AEMFC anion exchange membranes lack mechanical properties and chemical stability under high temperature and high pH conditions, resulting in problems such as decreased conductivity and membrane rupture.

Method used

Prepared by crosslinked copolymers from poly(styrene-b-ethylene-co-butene-b-styrene) and poly(aryl piperidinium) through acylation reaction and carbonyl reduction reaction, forming high mechanical properties and alkaline-stable cross-linked copolymers as anion exchange membrane material.

Benefits of technology

High ionic conductivity, hydration and mechanical properties under high temperature and pH conditions are achieved, and the dimensional stability and electrochemical properties of the membrane are improved, making it suitable for fuel cell applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119256025A_ABST
    Figure CN119256025A_ABST
Patent Text Reader

Abstract

Provided is a novel crosslinked copolymer which has excellent mechanical properties, excellent alkali stability, and high ionic conductivity and degree of hydration, and which can be preferably used as an anion exchange membrane (AEM) material for fuel cells and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of Korean Patent Application No. 10-2022-0079130 filed in the Korean Intellectual Property Office on June 28, 2022, and Korean Patent Application No. 10-2023-0040300 filed in the Korean Intellectual Property Office on March 28, 2023, the disclosures of which are incorporated herein by reference in their entirety.

[0003] The present invention relates to a cross-linked copolymer, a polymer membrane comprising the cross-linked copolymer, and an anion exchange membrane comprising the polymer membrane. Background Art

[0004] Hydrogen fuel cells are gaining attention as an environmentally friendly energy source because these cells only release water (H2O) as a byproduct when generating electricity. Among various hydrogen fuel cells, anion exchange membrane fuel cells (AEMFC) have become the focus of recent attention as an alternative technology to proton exchange membrane fuel cells (PEMFC) because they can use non-precious metal catalysts.

[0005] AEMFC conducts hydroxide ions (OH) through an anion exchange polymer electrolyte membrane - ), converting chemical energy into electrical energy. Therefore, in order to develop AEMFC with excellent performance, it is necessary to develop anion exchange polymer electrolyte membrane with excellent ion conductivity, also known as anion exchange membrane (AEM). However, AEMFC conducts OH - ions to generate electricity, so the pH value tends to rise during battery operation, resulting in an alkaline environment.

[0006] Generally, AEMs are composed of a polymer backbone and ion-conducting head groups, and the presence of a large amount of hydroxide ions in an alkaline environment provides opportunities for nucleophilic attacks on the polymer backbone and ion-conducting groups, resulting in a decrease in the ionic conductivity and mechanical properties of AEMs. Therefore, it is necessary to develop AEMs with excellent chemical stability to prevent this performance degradation. In other words, the development of AEMs with excellent ionic conductivity and chemical stability is crucial for the development of AEMFCs with excellent performance.

[0007] For ion-conducting polymers (ionomers) such as AEMs, ionic conductivity is mainly affected by the type of ion-conducting groups and ion exchange capacity (IEC). In addition, the effective formation of ion clusters and ion-conducting channels according to the morphology of the corresponding membrane also affects ionic conductivity.

[0008] The alkaline stability of AEMs is affected by a combination of factors, including the polymer backbone, ion-conducting groups, and hydration number. Therefore, improving the overall performance of AEMs (i.e., having high conductivity and alkaline stability) requires a comprehensive understanding of their properties: not only the types of ion-conducting groups and polymer backbones, but also the morphology of the corresponding membranes determined by their molecular structure and hydration number. To this end, a large number of studies have been conducted on the ion-conducting groups and polymer backbones of AEMs in the past decade.

[0009] First, regarding the ion-conductive groups and polymer backbones in terms of the AEM structure, quaternary ammonium salts such as benzyl ammonium and alkyl ammonium and cyclic ammonium such as imidazolium, piperidinium, and spiroammonium have been actively studied. In particular, piperidinium has received a lot of attention in recent years due to its moderate ionic conductivity and excellent chemical stability. Poly(aryl ether sulfone) (PES), poly(aryl ether ketone) (PAEK), poly(phenylene oxide) (PPO), spirobisindane, polyphenylene (PP), styrene-ethylene-butylene-styrene (SEBS), etc. have been actively studied as polymer backbones constituting AEMs. In particular, polyphenylene polymer backbones with an aryl ether-free structure have been extensively studied recently due to their excellent chemical stability and mechanical properties.

[0010] In addition to improving the properties of AEMs due to their structure, various approaches have been proposed, such as improving conductivity by introducing polycations and controlling the morphology of the membranes by introducing block, graft, or partially fluorinated polymer backbones or side chains and cross-linking to maximize stability.

[0011] Therefore, by controlling the structure of the ion-conducting group and the polymer and optimizing the morphology of the polymer membrane, AEM materials having excellent chemical stability even under high temperature and high pH conditions and AEM materials having very high battery performance almost equivalent to PEMFC (proton exchange membrane fuel cell) are being developed. Examples thereof include poly(aryl piperidinium) (PAP), poly(diphenylethane-co-terphenyl piperidinium) (PDTP), polycarbazole, poly(aryl-co-terphenyl piperidinium), and the like.

[0012] These polyphenylene-based AEMs are characterized by relatively low water uptake (WU), i.e., low hydration number, compared to what would be expected for their IEC. Water is usually used as the OH in the ion conduction mechanism of AEMs. - Therefore, high water absorption (WU) must be accompanied by the high ion conductivity of the AEM. In addition, when the membrane has a high hydration number, it also has the advantage of limiting the ion conductivity of the membrane by limiting the OH - The advantage of AEMs is that they ultimately improve the chemical stability of AEMs due to the nucleophilic attack of conductive groups. In addition, due to the strong π-π interaction between the phenyl groups contained in the polymer backbone, AEMs based on polyphenylene have high stress and relatively low strain characteristics. In addition, AEMs must not be damaged by airflow or impact because they act as diaphragms, preventing the fuel supplied to the anode and cathode from passing to the opposite electrode. Therefore, in order to ensure the performance and durability of AEMFCs, the high mechanical stability of AEMs, especially the high stress characteristics, are obviously indispensable. However, in order to overcome the mechanical failure that may occur at the edge of the active area of ​​MEA where the mechanical stress is maximized during the operation of AEMPC, AEMs are required to have high stress and high strain characteristics.

[0013] Meanwhile, AEMs based on styrene-b-ethylene-co-butylene-b-styrene (SEBS) have different physical properties from those based on polyphenylene, namely, high hydration number and high strain. This is attributed to the aliphatic chain structure of SEBS. In addition, SEBS has a fully developed morphology with a block copolymer structure of styrene and 1,4-butadiene, so this AEM has higher ionic conductivity and chemical stability than expected for its IEC. However, due to excessive swelling of the AEM and reduced conductive ion OH - The so-called "dilution effect" of concentration, excessive water absorption may reduce the ion conduction properties of the membrane. In addition, SEBS has low tensile strength and is prone to membrane rupture and deformation, making it unsuitable for the high temperature and humid AEMFC operating environment. In addition, the limited solubility of SEBS restricts the modification of SEBS, making it difficult to develop SEBS-based AEMs with better performance.

[0014] To overcome these limitations of SEBS, Korean Patent No. 10-2184530 proposed a copolymer (xTQA-PPO-SEBS) in which flexible SEBS and rigid PPO were cross-linked by triazole. Compared with previous SEBS-based membranes, the copolymer exhibited low WU and high deformability, and showed higher ionic conductivity and battery characteristics than expected for its IEC. However, since the copolymer contains an aryl ether structure, it has a problem of low chemical stability to hydroxide ions.

[0015] Prior art literature

[0016] Patent Document 1: Korean Patent Registration No. 10-2184530

[0017] Non-patent document 1: Nat. Energy 4 (2019) 392–398

[0018] Non-patent literature 2: J. Power Sources 487 (2021), 229429

[0019] Non-patent literature 3: J. Mater. Chem. A. Mater. 9 (2021) 327–337

[0020] Non-patent document 4: Nat. Commun. 12 (2021) 2367

[0021] Non-patent literature 5: J. Membr. Sci. 621 (2021)

[0022] Non-patent literature 6: J. Membr. Sci. 642 (2022), 119966

[0023] Non-patent literature 7: J. Polym. Sci. 58 (2020) 2181–2196

[0024] Non-patent document 8: Int. J. Hydrogen Energy 46 (2021) 36301–36313

[0025] Non-patent literature 9: J. Membr. Sci. 599 (2020), 117829

[0026] Non-patent literature 10: Int. J. Hydrogen Energy 45 (2020) 15658–15671

[0027] Non-patent literature 11: J. Membr. Sci. (2022), 120029

[0028] Non-patent literature 12: J. Mater. Chem. A. 7 (2019) 6883–6893

[0029] Non-patent literature 13: J. Membr. Sci. 638 (2021), 119685

[0030] Non-patent literature 14: Energy Environ. Sci. 13 (2020) 3633–3645

[0031] Non-patent literature 15: Int. J. Hydrogen Energy 46 (2021) 18524–18533

[0032] Non-patent literature 16: J. Membr. Sci. 647 (2022), 120341

[0033] Non-patent literature 17: Angew. Chem. 133 (2021) 7789–7797

[0034] Non-patent literature 18: Membranes 10 (2020) 1–16 Summary of the invention

[0035] Technical issues

[0036] The present invention relates to a novel cross-linked copolymer which can be preferably used as an anion exchange membrane (AEM) material for fuel cells due to its excellent mechanical properties, excellent alkaline stability, and high ionic conductivity and hydration degree.

[0037] Technical Solution

[0038] According to one embodiment of the present invention, there is provided a cross-linked copolymer including a first chain represented by the following Chemical Formula 1 and a second chain represented by the following Chemical Formula 2, wherein the first chain and the second chain are cross-linked with each other:

[0039] [Chemical formula 1]

[0040]

[0041] In Chemical Formula 1,

[0042] * is the bonding position with Chemical Formula 2,

[0043] The sum of q1, q2, q5 and q6 is an integer from 100 to 1000,

[0044] The sum of q3 and q4 is an integer from 150 to 2000,

[0045] a and b are each independently an integer from 3 to 10, and

[0046] R1 to R4 are each independently hydrogen or -(CH2) p -CH3, wherein p is an integer from 0 to 5,

[0047] [Chemical formula 2]

[0048]

[0049] In chemical formula 2,

[0050] * is the bonding position with Chemical Formula 1,

[0051] x and y are each independently an integer from 0 to 10, and

[0052] n is an integer from 10 to 1,000.

[0053] Furthermore, according to one embodiment of the present disclosure, a polymer film including the above cross-linked copolymer is provided.

[0054] In addition, according to one embodiment of the present disclosure, there is provided a method for preparing a cross-linked copolymer, comprising the following steps:

[0055] (a) preparing a polymer represented by the following chemical formula 1-1;

[0056] (b) preparing a polymer represented by the following Chemical Formula 2-1; and

[0057] (c) preparing a cross-linked copolymer by cross-linking a polymer represented by the following Chemical Formula 1-1 and a polymer represented by the following Chemical Formula 2-1:

[0058] [Chemical formula 1-1]

[0059]

[0060] In Chemical Formula 1-1,

[0061] The sum of q1, q2, q5 and q6 is an integer from 100 to 1000,

[0062] The sum of q3 and q4 is an integer from 150 to 2000,

[0063] a and b are each independently an integer from 3 to 10,

[0064] R1 to R4 are each independently hydrogen or -(CH2) p -CH3, wherein p is an integer from 0 to 5, and

[0065] X1 and X2 are each independently a halogen group,

[0066] [Chemical formula 2-1]

[0067]

[0068] In chemical formula 2-1,

[0069] x and y are each independently an integer from 0 to 10, and

[0070] n is 10 to 1000.

[0071]

Beneficial Effects

[0072] The cross-linked copolymer of the present invention has excellent dimensional stability while having high water absorption (WU), and exhibits high ionic conductivity, hydration degree and alkaline stability. In addition, the cross-linked copolymer has excellent mechanical properties, such as tensile strength and elongation properties.

[0073] As described above, the cross-linked copolymer of the present invention has excellent electrochemical and mechanical properties, and thus can be suitably used as an anion exchange membrane material. BRIEF DESCRIPTION OF THE DRAWINGS

[0074] Figure 1 The x-PBB-SEBS membranes of Examples 1 to 3 and the OH reported in the literature are shown. - Figure 2. Hydration number (λ) vs. IEC plots of SEBS-based AEMs (open symbols) and poly(phenylene)-based AEMs (closed symbols) at room temperature.

[0075] Figure 2 (a) TGA graphs from 30°C to 250°C and (b) DSC graphs from -20°C to 10°C of the x-PBB-SEBS films of Examples 1 to 3 are shown.

[0076] Figure 3 The x-PBB-SEBS membranes of Examples 1 to 3 show (a) hydroxide ion conductivity (solid line) and normalized conductivity (dashed line), and (b) normalized conductivity at 60° C. and 95% RH conductivity.

[0077] Figure 4 Shown are (a) an AFM image of 30x-PBB-SEBS, (b) an AFM image of 40x-PBB-SEBS, (c) an AFM image of 50x-PBB-SEBS, (d) a TEM image of 30x-PBB-SEBS, (e) a TEM image of 40x-PBB-SEBS, and (f) a TEM image of 50x-PBB-SEBS.

[0078] Figure 5 Shown are (a) OH ion conductivity retention and (b) IEC retention of x-PBB-SEBS membranes after treatment with 2 M KOH at 80 °C.

[0079] Figure 6 It is shown that x-PBB-SEBS membrane has good thermal conductivity at 60℃ and H2 / O2 200 / 400mL min -1 Single cell performance under (a) 100% / 100% RH and (b) 70% / 100% RH conditions.

[0080] Figure 7 shows that poly(bibenzyl N-methylpiperidine) 21 H NMR spectroscopy.

[0081] Figure 8 Shown are (a) bromohexyl SEBS 4 and (b) bromohexyl SEBS 3 1 H NMR spectroscopy.

[0082] Fig. 9 Images of cross-linked (bibenzyl N-methylpiperidinium)-SEBS membranes (x-PBB-SEBS) with different degrees of cross-linking are shown.

[0083] Fig.10 Infrared spectra of x-PBB-SEBS films before (dashed line) and after (solid line) TMA treatment are shown.

[0084] Fig.11 The mechanical properties of x-PBB-SEBS films at 50% RH are shown.

[0085] Fig.12 It shows that x-PBB-SEBS membrane is similar to OH - Comparison of Young's modulus and elongation at break between typical AEMs of the form (the inset shows the elongation at break from 0% to 150%).

[0086] Fig.13 (a) Thermogravimetric analysis (TGA) and (b) differential scanning calorimetry (DSC) curves of x-PBB-SEBS membrane are shown.

[0087] Fig.14 Shown is the normalized conductivity of the x-PBB-SEBS membrane at room temperature compared with the normalized conductivity of representative membranes reported in the literature.

[0088] Fig.15 Shown are the TGA curves of the 40x-PBB-SEBS film before and after oxidation stability testing in the temperature range of 30°C to 800°C.

[0089] Fig.16 It shows that at 60 °C and H2 / O2 200 / 400 mL min -1 Comparison of the maximum power density of x-PBB-SEBS membrane under 100% / 100% A / C RH (red) and 70% / 100% A / C RH (blue) conditions. DETAILED DESCRIPTION

[0090] The terminology used herein is for describing particular embodiments only and is not intended to be limiting of the present invention. Unless the context clearly indicates otherwise, singular forms also include plural forms.

[0091] It should be further understood that when the terms “include,” “comprises,” or “has” are used in the present disclosure, they specify the presence of stated features, steps, components, or a combination thereof, but do not preclude the presence or addition of one or more other features, steps, components, or a combination thereof.

[0092] Although the present invention can be variously modified and has various forms, its specific implementation will be shown by example and will be described in detail. However, it is not intended to limit the present invention to the specific form disclosed, and it should be understood that the present invention includes all modifications, equivalents and substitutes within the scope of the thought and technology of the present invention.

[0093] Hereinafter, the present invention will be described in detail.

[0094] According to one embodiment of the present invention, there is provided a cross-linked copolymer, comprising a first chain represented by the following Chemical Formula 1 and a second chain represented by the following Chemical Formula 2, wherein the first chain and the second chain are cross-linked with each other:

[0095] [Chemical formula 1]

[0096]

[0097] In Chemical Formula 1,

[0098] * is the bonding position with Chemical Formula 2,

[0099] The sum of q1, q2, q5 and q6 is an integer from 100 to 1000,

[0100] The sum of q3 and q4 is an integer from 150 to 2000,

[0101] a and b are each independently an integer from 3 to 10, and

[0102] R1 to R4 are each independently hydrogen or -(CH2) p -CH3, wherein p is an integer from 0 to 5,

[0103] [Chemical formula 2]

[0104]

[0105] In chemical formula 2,

[0106] * is the bonding position with Chemical Formula 1,

[0107] x and y are each independently an integer from 0 to 10, and

[0108] n is an integer from 10 to 1,000.

[0109] The cross-linked copolymer of the present invention is characterized in that a first chain based on poly(styrene-b-ethylene-co-butylene-b-styrene) (SEBS) is cross-linked with a second chain based on poly(arylpiperidinium).

[0110] The first chain of the cross-linked copolymer has elasticity, the second chain has rigidity, and both the first chain and the second chain show phase separation. Since the first chain and the second chain are chemically cross-linked, the cross-linked copolymer of the present invention shows excellent mechanical properties, namely high elongation at break and Young's modulus and appropriate tensile strength.

[0111] In addition, due to the above structural characteristics, the cross-linked copolymer has excellent water retention capacity, high ion conductivity and excellent alkaline stability. Therefore, the cross-linked copolymer can be suitably used as an anion exchange membrane for fuel cells and the like.

[0112] The ratio of the first chain represented by Chemical Formula 1 to the second chain represented by Chemical Formula 2 can be adjusted according to the desired physical properties. For example, in the cross-linked copolymer, based on 100 moles of the first chain, the content of the second chain can be more than 10 moles, more than 20 moles, more than 30 moles, more than 40 moles, and less than 70 moles, less than 60 moles, less than 50 moles. When the ratio of the first chain to the second chain in the cross-linked copolymer meets the above range, excellent mechanical properties and electrochemical properties can be achieved.

[0113] Preferably, the sum of q1, q2, q5, and q6 can be an integer greater than 100, greater than 150, greater than 200, greater than 250, greater than 300, greater than 350, greater than 400, greater than 450, or greater than 500, and less than 1000, less than 950, less than 900, less than 850, or less than 800.

[0114] Preferably, the sum of q3 and q4 can be an integer of greater than 150, greater than 200, greater than 250, greater than 300, greater than 350, greater than 400, greater than 450, greater than 500, greater than 550, or greater than 600, and less than 2000, less than 1800, less than 1600, less than 1500, less than 1400, less than 1200, or less than 1000.

[0115] Preferably, q1 to q6 may each independently be an integer of 10 or more, 20 or more, 25 or more or 30 or more, and 500 or less, 450 or less, 400 or less, 350 or less or 300 or less.

[0116] Preferably, the ratio of the sum of q1, q2, q5 and q6 to the sum of q1 to q6, that is, the total mole fraction of the styrene-derived repeating units relative to all repeating units in Chemical Formula 1 may be 0.2 or more, 0.25 or more, or 0.3 or more, and 0.5 or less, or 0.45 or less.

[0117] Preferably, the ratio of the sum of q1 and q6 to the sum of q1, q2, q5 and q6 in Chemical Formula 1, that is, the total molar fraction of the unsubstituted styrene repeating units relative to all styrene-derived repeating units in Chemical Formula 1 may be 0.2 or more, 0.25 or more, 0.3 or more or 0.35 or more, and 0.5 or less, 0.45 or less or 0.4 or less.

[0118] Preferably, a and b may each independently be an integer of 3 or more, or 4 or more, and 10 or less, 9 or less, 8 or less, 7 or less, or 6 or less.

[0119] Preferably, R1 to R4 are each independently hydrogen or -(CH2) x -CH3, and x may be an integer from 0 to 3, or an integer from 0 to 2. Preferably, R1 to R4 may all be hydrogen.

[0120] Preferably, n is an integer of 10 or more, 100 or more, or 150 or more, and 1000 or less, or 500 or less.

[0121] Preferably, x is an integer of 1 or more, or 2 or more, and 9 or less, 7 or less, 5 or less, 4 or less, or 3 or less.

[0122] Preferably, y is an integer of 0 or more and 7 or less, 5 or less, 3 or less, or 2 or less.

[0123] Specifically, the cross-linked copolymer may include a repeating unit represented by the following Chemical Formula 3:

[0124] [Chemical formula 3]

[0125]

[0126] In Chemical Formula 3, q1 to q6, a, b, x, y and n are as defined in Chemical Formulas 1 and 2.

[0127] Preferably, the cross-linked copolymer may include a repeating unit represented by the following Chemical Formula 4:

[0128] [Chemical formula 4]

[0129]

[0130] In Chemical Formula 4, q1 to q6 and n are as defined in Chemical Formulas 1 and 2.

[0131] The cross-linked copolymer has a positively charged quaternary ammonium group, which can selectively pass only anions. Therefore, the cross-linked copolymer can be used as an anion exchange membrane. The counter ion (anion) group of the cation (quaternary ammonium group) of the cross-linked copolymer can be OH - , Cl -Br - or HCO3 - , preferably OH - .

[0132] Furthermore, the cross-linked copolymers exhibited excellent ion conduction efficiency and alkaline stability due to the phase separation characteristics.

[0133] Therefore, according to one embodiment of the present disclosure, a polymer film including the cross-linked copolymer is provided.

[0134] The thickness of the polymer film comprising the cross-linked copolymer may be 20 μm or more, 30 μm or more, 45 μm or more, or 55 μm or more, and 70 μm or less, 60 μm or less, or 55 μm or less. When the thickness of the polymer film satisfies the above range, it exhibits high mechanical properties and excellent electrochemical properties, making it suitable for use as an anion exchange membrane.

[0135] Since the polymer membrane includes the cross-linked copolymer comprising the first chain and the second chain, it has improved mechanical strength compared to conventional polymers used for AEM, exhibits high ionic conductivity while exhibiting appropriate IEC, and has good alkaline stability. Therefore, the polymer membrane having the above physical properties can be suitable for use as an anion exchange membrane in a fuel cell, etc.

[0136] At the same time, according to one embodiment of the present disclosure, a method for preparing the cross-linked copolymer is provided. Specifically, the method for preparing the cross-linked copolymer comprises the following steps:

[0137] (a) preparing a polymer represented by the following chemical formula 1-1;

[0138] (b) preparing a polymer represented by the following Chemical Formula 2-1; and

[0139] (c) preparing a cross-linked copolymer by cross-linking a polymer represented by the following Chemical Formula 1-1 and a polymer represented by the following Chemical Formula 2-1:

[0140] [Chemical formula 1-1]

[0141]

[0142] In Chemical Formula 1-1,

[0143] The sum of q1, q2, q5 and q6 is an integer from 100 to 1000,

[0144] The sum of q3 and q4 is an integer from 150 to 2000,

[0145] a and b are each independently an integer from 3 to 10,

[0146] R1 to R4 are each independently hydrogen or -(CH2) p -CH3, wherein p is an integer from 0 to 5, and

[0147] X1 and X2 are each independently a halogen group,

[0148] [Chemical formula 2-1]

[0149]

[0150] In chemical formula 2-1,

[0151] x and y are each independently an integer from 0 to 10, and

[0152] n is 10 to 1000.

[0153] Preferred ranges of q1 to q6, a, b, R1 to R4, x, y and n in Chemical Formulas 1-1 and 2-1 are the same as those described in Chemical Formulas 1 and 2 above.

[0154] X1 and X2 are each independently F, Cl, Br or I, preferably Br.

[0155] Step (a) is a step of introducing a halogen alkyl group into the styrene portion of the SEBS polymer. Specifically, the poly(styrene-b-ethylene-co-butylene-b-styrene)-based polymer represented by Chemical Formula 1-1 can be prepared by a Friedel-Crafts acylation reaction of SEBS and a reduction reaction of the carbonyl group.

[0156] The acyl halide used in the acylation reaction is selected based on the number of a and b. Specifically, the acyl halide can be XR-COCl (wherein X is a halogen and R is C 1-29 When a and b are different from each other or X1 and X2 are different from each other, the acylation reaction may be carried out two or more times using different types of acyl halides.

[0157] The acylation reaction may use aluminum chloride (AlCl 3 ) as a catalyst, and the reaction may be carried out at 20 to 30° C. for 8 to 24 hours.

[0158] The reduction reaction of the carbonyl group can be carried out using methods known in the art without limitation. For example, the carbonyl group can be reduced by adding triethylsilane and trifluoroacetic acid and then reacting at 90 to 120° C. for 20 to 30 hours. Through this reaction, a polymer based on poly(styrene-b-ethylene-co-butylene-b-styrene) represented by Chemical Formula 1-1 can be obtained.

[0159] Preferably, the copolymer based on poly(styrene-b-ethylene-co-butylene-b-styrene) contains 30 moles or more, 40 moles or more, 50 moles or more, 55 moles or more, or 60 moles or more, and 90 moles or less, 80 moles or less, 75 moles or less, 70 moles or less, or 65 moles or less of halogen groups based on 100 moles of styrene repeating units. The moles of halogen groups relative to the styrene repeating units can be adjusted by adjusting the moles of acyl halide relative to the moles of styrene in the SEBS polymer during the acylation reaction.

[0160] Step (b) is a step of preparing a poly(arylpiperidinium)-based polymer. For example, by reacting an aryl compound ( wherein x is as described in Chemical Formula 2) and N-alkyl-4-piperidone can react to prepare a polymer represented by Chemical Formula 2-1. The reaction can be carried out at, for example, -10 to 10°C for 12 to 60 hours.

[0161] Step (c) is a step of preparing a crosslinked copolymer by crosslinking the polymer represented by Chemical Formula 1-1 and the polymer represented by Chemical Formula 2-1. Since the polymer represented by Chemical Formula 1-1 contains a halogen group and the polymer represented by Chemical Formula 2-1 contains a tertiary amine group, the two polymers can be easily crosslinked by a nucleophilic substitution reaction without a separate crosslinking agent.

[0162] In step (c), the amount of the polymer represented by Chemical Formula 2-1 is preferably 10 mol or more, 20 mol or more, 30 mol or more, or 40 mol or more, and 70 mol or less, 60 mol or less, or 50 mol or less, based on 100 mol of the halogen groups contained in the polymer represented by Chemical Formula 1-1. When this molar ratio is met, the prepared cross-linked polymer may have an appropriate ratio of the first chain to the second chain, thereby exhibiting excellent hydroxide ion conductivity and mechanical properties.

[0163] The reaction in step (c) can be carried out at 40 to 60° C. for 10 to 16 hours, preferably at 45 to 55° C. for 11 to 13 hours. When the polymerization temperature is lower than 40° C. or the reaction time is less than 10 hours, the cross-linking reaction between the polymers does not occur sufficiently, so the hydroxide ion conductivity may decrease, thereby reducing the alkaline stability. On the contrary, when the polymerization temperature exceeds 60° C. or the reaction time exceeds 16 hours, the degree of cross-linking between the polymers increases excessively, resulting in gelation of the cross-linked polymer solution.

[0164] Meanwhile, after step (c), a step (d) of reacting the cross-linked copolymer with trimethylamine may be further included to convert all the halogen groups remaining in the cross-linked copolymer into amine groups. Step (d) may be performed at 40 to 60° C. for 10 to 30 hours, preferably at 45 to 55° C. for 20 to 30 hours.

[0165] As described above, since the present invention introduces a halogen functional group into the SEBS main chain and reacts with the amine-containing polymer represented by Chemical Formula 2-1 to prepare a cross-linked copolymer, the polymer can be quantitatively cross-linked without side reactions, and the degree of cross-linking can be easily controlled by adjusting the amount of each polymer.

[0166] Furthermore, according to the above method, the cross-linked copolymer can be prepared more simply and with high yield, thereby improving the productivity of the process and reducing the cost.

[0167] The present invention is described in more detail below by way of examples. However, the following examples are only used to illustrate the present invention, and the scope of the present invention is not limited thereto.

[0168] [Example]

[0169] <Materials>

[0170] Bibenzyl (99%), aluminum chloride (99%), 6-bromohexanoyl chloride, N-methyl-4-piperidone (97%), and trimethylamine solution (45 wt% in water) were purchased from Sigma-Aldrich (St. Louis, MO, USA). Trifluoromethanesulfonic acid (98%) was obtained from TCI (Tokyo, Japan). Triethylsilane (98%) was obtained from Alfa Aesar (MA, USA). Trifluoroacetic acid was obtained from Daejung Chemicals & Metals (Siheung, South Korea). Poly(styrene-b-ethylene-co-butylene-b-styrene) (SEBS, A1535H) with a styrene content of 57% was obtained from Kraton (Houston, TX, USA). All other chemicals were obtained from other commercial sources.

[0171] <Identification of polymer chemical structure>

[0172] The chemical structures of the polymers obtained in each step in the following examples are shown in 1 The proteins were identified by H NMR and Fourier transform infrared (FTIR) spectroscopy. 1 H NMR spectra were obtained using a 400 MHz NMR instrument (Agilent 400-MR) using CDCl3 as solvent. FTIR spectra were obtained using a PerkinElmer Spectrum Two ATR-FTIR spectrometer. The spectra were collected from 4000 to 400 cm -1 .

[0173] Example 1: Preparation of 30x-PBB-SEBS (crosslinking degree: 30%) membrane

[0174] (1) Synthesis of poly(bibenzyl N-methylpiperidinium) 2

[0175]

[0176] (In the above reaction formula, n is 158.)

[0177] Bibenzyl (3.00 g, 16.46 mmol) and N-methyl-4-piperidone (2.23 g, 19.75 mmol) were poured into a completely dry 50 mL round-bottom flask under a nitrogen atmosphere and then dissolved in dichloromethane (20 mL) using a magnetic stirrer. After the mixture was fully dissolved, the solution was cooled to 0 °C with an ice bath. Next, trifluoroacetic acid (2.82 g, 24.69 mmol) and trifluoromethanesulfonic acid (24.70 g, 164.60 mmol) were slowly added to the solution under constant stirring. The color of the solution changed from light brown to dark brown. After 48 hours, the viscous solution was poured into a large amount of KOH solution (500 mL), the precipitated polymer was filtered onto filter paper, and washed several times with deionized (DI) water to remove any residual reactants. The obtained polymer was dried in a vacuum oven at 80°C for 24 hours to obtain a yellow powder, which was confirmed to be poly(bibenzyl N-methylpiperidine) (4.51 g, 98.8%); δ H (400MHz,CDCl3)7.85–6.73(8H,wide signal,H 1,2 ),3.05–2.67(4H,d,H 3,3’ ),2.60–2.13(8H,wide signal,H 5,5’,6 ),2.12–1.67(4H,d,H 4,4’ )( Figure 7 ).

[0178] (2) Synthesis of Bromohexyl SEBS 3

[0179] (2-1) Synthesis of Bromohexanoyl SEBS 4

[0180]

[0181] (In the above reaction formula, the sum of q1, q2, q5, and q6 is 711, the sum of q3 and q4 is 996, and the ratio of the sum of q1 and q6 to the sum of q1, q2, q5, and q6 is 0.3.)

[0182] Under nitrogen protection, SEBS (10.00 g, 54.73 mmol) was poured into a 1000 mL two-necked round-bottom flask and dissolved in dichloromethane (320 mL) with a magnetic stirrer. After the polymer was fully dissolved, aluminum chloride (5.47 g, 41.05 mmol) and 6-bromohexanoyl chloride (8.76 g, 41.05 mmol) dissolved in dichloromethane (80 mL) were slowly added with a dropping funnel. After 24 hours, the reaction mixture was poured into a large amount of ethanol (1500 mL), and the precipitated polymer was filtered with filter paper and washed with ethanol several times to remove any residual reactants. The resulting polymer was dried at room temperature in a dryer for 24 hours to obtain a white rubbery product, which was confirmed to be bromohexanoyl SEBS 4, in which the bromohexanoyl-functionalized side chain was bonded to 70 mol% (16.40 g, 97.7%) of the total 100 mol% styrene in SEBS; δ H (400MHz,CDCl3)7.92–7.37(4H,broad signal,H 1,2 ),7.26–6.28(10H,wide signal,H 3,4 ),3.50–3.38(3H,broad signal,H 10 ),3.03–2.80(3H,broad signal,H6),2.69–2.35(2H,broad signal,H 12 ),2.01–0.56(46H,wide signal,H 7-9,11,13-18 )( Figure 8 a).

[0183] (2-2) Synthesis of Bromohexyl SEBS 3

[0184]

[0185] (In the above reaction formula, the sum of q1, q2, q5, and q6 is 711, the sum of q3 and q4 is 996, and the ratio of the sum of q1 and q6 to the sum of q1, q2, q5, and q6 is 0.3.)

[0186] Under nitrogen protection, bromohexyl SEBS 4 (16.00 g, 38 mmol) was poured into a 1000 mL double-mouthed round-bottom flask connected to a reflux condenser and equipped with a magnetic stirrer, and then dissolved in chloroform (320 mL). After the polymer was fully dissolved, triethylsilane (60.70 mL, 380 mmol) and trifluoroacetic acid (58.16 mL, 760 mmol) were added. The reaction mixture was slowly heated to 105 ° C and placed at this temperature for 24 hours. The reaction mixture was cooled to room temperature and 1M KOH (400 mL) was added to neutralize the solution. The organic layer was poured into methanol (1500 mL), and the precipitated polymer was filtered onto filter paper and washed several times with methanol to remove any residual reactants. The resulting polymer was dried in a dryer at room temperature for 24 hours to obtain a white rubber product bromohexyl SEBS 3 (15.28 g, 93.11%); δ H (400MHz,CDCl3)7.21–6.27(12H,wide signal,H 1-4 ),3.48–3.34(3H,broad signal,H 10 ),2.66–2.27(5H,wide signal,H 6’,12 ),1.99–0.59(46H,wide signal,H 6-9,11,13-18 )( Figure 8 b).

[0187] (3) Preparation of cross-linked poly (bibenzyl N-methylpiperidinium)-SEBS1 membrane (30x-PBB-SEBS)

[0188]

[0189] (In the above reaction formula, n is 158, the sum of q1, q2, q5, and q6 is 711, the sum of q3 and q4 is 996, and the ratio of the sum of q1 and q6 to the sum of q1, q2, q5, and q6 is 0.3.)

[0190] Poly(bibenzyl N-methylpiperidine) 2, bromohexyl SEBS 3 and HPLC grade chloroform (20 mL) were placed in a 20 mL vial and the mixture was stirred until a homogeneous solution was obtained. Here, poly(bibenzyl N-methylpiperidine) 2 was used in a ratio of 30 mol% relative to 100 mol% of bromohexyl SEBS 3.

[0191] The polymer solution was heated at 40 °C overnight (12 h) to induce crosslinking. The polymer solution was cooled to room temperature, poured into a glass Petri dish equipped with a cotton filter, and then dried at room temperature for 24 h. The prepared membrane was peeled off from the Petri dish and immersed in deionized water to wash away any residual solvent. Next, the membrane was immersed in a trimethylamine (TMA) solution at 45 °C for 24 h and washed with deionized water to remove excess TMA. Thereafter, the membrane was immersed in a 1 M KOH solution at room temperature for at least 24 h to remove the Br - Ion exchange for OH - ions and washed several times with deionized water to remove excess KOH, thus obtaining a 30x-PPB-SEBS membrane.

[0192] In order to confirm that Br in the cross-linked film was replaced by TMA, the infrared changes before and after trimethylamine (TMA) treatment were confirmed ( Fig.10 ). It was confirmed that after TMA treatment, about 642cm -1 The C-Br peak at 40° disappeared, confirming that the C-Br bond in x-PBB-SEBS was replaced by TMA.

[0193] Example 2: Preparation of 40x-PBB-SEBS (crosslinking degree: 40%) membrane

[0194] A 40x-PBB-SEBS membrane was prepared in the same manner as in Example 1, except that poly(bibenzyl N-methylpiperidine) 2 was used in an amount of 40 mol % relative to bromohexyl SEBS 3 in step (3).

[0195] Example 3: Preparation of 50x-PBB-SEBS (crosslinking degree: 50%) membrane

[0196] A 50x-PBB-SEBS membrane was prepared in the same manner as in Example 1, except that poly(bibenzyl N-methylpiperidine) 2 was used in an amount of 50 mol % relative to bromohexyl SEBS 3 in step (3).

[0197] In Examples 1 to 3, a flexible film having a thickness of 30 to 35 μm ( Fig. 9 ).

[0198] Experimental Example 1: Ion Exchange Capacity (IEC), Water Absorption (WU) and Swelling Ratio (SR)

[0199] (1) Ion exchange capacity (IEC)

[0200] a. Experimental IEC

[0201] The ion exchange capacity (IEC) of each membrane was measured using the back titration method. -The film was placed in a 0.01M HCl standard solution for 24 hours. The residual HCl was back-titrated with a 0.01M NaOH standard solution using a phenolphthalein indicator. The film was then dried to measure its weight (W 干 , g). The experimental IEC (meq g) was calculated using the following formula -1 ), which is the number of moles of exchangeable hydroxide ions per gram:

[0202] IEC(meq g -1 )=(C0V0-C0V x ) / W 干

[0203] Where V0 and V x are the volume of NaOH before titration and the volume of NaOH consumed in titration, respectively; C0 is the concentration of NaOH used in back titration; W 干 is the weight of the film after drying in an oven for at least 12 hours.

[0204] b. Theoretical IEC

[0205] The theoretical IEC value is based on the number of Br atoms contained in bromohexyl SEBS 3 (which is 1 H NMR spectra), and the masses of the two polymers (2 and 3) used in the cross-linking process were determined.

[0206] (2) Water absorption (WU) and expansion rate (SR)

[0207] The water absorption rate (WU, %) and the swelling rate (SR, %) were calculated by immersing each circular film in Examples 1 to 3 in water at 20°C and 80°C. - The membrane was immersed in deionized water for at least 24 h, the surface of the membrane was wiped, and the weight (W) was quickly measured. 湿 ), length (L 湿 ) and thickness (T 湿 The film was dried under vacuum for 24 h, and the weight of the dry film (W 干 ), length (L 干 ) and thickness (T 干 ). Use the following formula to determine water absorption (%) and expansion (%):

[0208] WU(%)=(W 湿 -W 干 ) / W 干 ×100

[0209] SR(%)=(L 湿 -L 干 ) / L 干 ×100 or (T 湿 -T干 ) / T 干 ×100

[0210] The hydration number (λ) of each membrane was calculated from the WU and experimental IEC of each membrane. The hydration number was determined using the following formula:

[0211] Hydration number (λ) = (water absorption (%) × 1000) / (IEC × 18)

[0212] (3) Results

[0213] The IEC, WU and SR of the x-PBB-SEBS films of Examples 1 to 3 are listed in Table 1 below.

[0214]

Table 1

[0215]

[0216] a according to 1 Theoretical IEC values ​​calculated from H NMR spectra

[0217] b Experimental IEC values ​​measured by back titration

[0218] IEC is defined as the milliequivalents of ion-conducting groups per unit mass of a polymer electrolyte membrane. In general, the higher the IEC of a polymer electrolyte membrane, the more water the membrane can hold (i.e., the higher the WU). Since water can serve as a medium for the conduction of hydroxide ions in an AEM, the higher the IEC, the higher the ionic conductivity. However, too high an IEC generally results in an increase in WU, which reduces ionic conductivity through a mechanism known as the "dilution effect." When this happens, the SR of the membrane also increases, which reduces its mechanical properties and dimensional stability. Therefore, in order for an AEM to have high ionic conductivity and good mechanical properties, its IEC needs to be appropriate.

[0219] The theoretical IEC of 30x-PBB-SEBS, 40x-PBB-SEBS, and 50x-PBB-SEBS are 1.96, 1.86, and 1.77 meq g, respectively. -1 , and decreases with the increase of cross-linking degree, because the total amount of introduced ion-conductive groups decreases with the decrease of bromohexyl SEBS 3 content. At the same time, it is confirmed that the experimentally measured IEC of x-PBB-SEBS membrane is close to the theoretical value, and the theoretical IEC value is equivalent to the experimentally measured IEC value, which also confirms that the cross-linking degree has reached the expected level.

[0220] Referring to the WU and SR results of x-PBB-SEBS membranes, both WU and SR decreased with increasing crosslinking degree, leading to improved dimensional stability. This effect is attributed to the reduction of the elastic polymer SEBS content and the influence of chemical bonds between polymer chains formed by crosslinking, which inhibits membrane expansion.

[0221] Next, the hydration number (λ value) of each film was calculated. As expected, the hydration number of x-PBB-SEBS decreased with increasing degree of crosslinking as follows: 30x-PBB-SEBS = 34.7, 40x-PBB-SEBS = 31.1, 50x-PBB-SEBS = 27.7.

[0222] The hydration numbers of the membranes according to Examples 1 to 3 were then compared with the hydration numbers of polyphenylene-based and SEBS-based membranes reported in previous studies (

[10] J. Mater. Chem. A. Mater. 9 (2021) 327–337;

[11] Nat. Commun. 12 (2021) 2367;

[32] Int. J. Hydrogen Energy 46 (2021) 36301–36313;

[33] J. Membr. Sci. 599 (2020), 117829;

[35] J. Membr. Sci. (2022), 120029;

[48] Korean Patent No. 10-2184530;

[53] J. Membr. Sci. 647 (2022), 120341) ( Figure 1 ).

[0223] The results show that the λ value of x-PBB-SEBS membranes is between that of SEBS-based AEMs (whose λ value is higher than the expected value of their IEC) and poly(phenylene)-based AEMs (whose λ value is lower than the expected value of their IEC). As mentioned above, water acts as a medium for ion conduction, so the hydration number should be high to achieve AEMs with high ionic conductivity. However, too high a hydration number may have a negative impact on ionic conductivity, so an appropriate value is necessary. Since x-PBB-SEBS membranes are prepared by cross-linking two polymers of different properties and adjusting the degree of cross-linking, their hydration number is easy to control.

[0224] Experimental Example 2: Mechanical and Thermal Properties

[0225] (1) Mechanical properties

[0226] A tabletop tensile tester (Shimadzu EZ-TEST E2-L, Kyoto, Japan) was used to test the tensile strength of the samples at 10 mm min at 25 °C and 50% relative humidity. -1 Crosshead velocity measurement OH -Mechanical properties of the membrane. The cross-sectional area of ​​the sample in its initial state is used to determine the engineering stress. The initial slope of the stress-strain curve is used to calculate the Young's modulus (E). For this test, a sample of each membrane was made into a dumbbell shape with a total area of ​​40×10mm and a test area of ​​20×10mm.

[0227] (2) Thermal stability

[0228] The thermal stability of the films was investigated by thermogravimetric analysis (TGA) using a Scinco TGA N-1000 instrument (Seoul, Korea). TGA was performed at 10 °C min-1 under nitrogen atmosphere. -1 The heating rate runs from 30 to 800 °C.

[0229] The glass transition temperature (Tg) of each film was measured by differential scanning calorimetry (DSC) using a PerkinElmer DSC 4000 (Waltham, MA, USA). Samples were prepared in aluminum pans and measured for two cycles from −40 to 200 °C with a heating and cooling rate of 10 °C min -1 The Tg was determined from the second heating cycle.

[0230] (3) Results

[0231] In AEMFC, AEM is used as electrolyte to convert OH generated at the cathode into - The AEM conducts ions to the anode. It also acts as a separator, preventing H2 and O2 (or air), used as fuel, from passing from one electrode to the other. Therefore, the AEM must have excellent mechanical and thermal properties to be highly resistant to damage or deformation under battery operating conditions (such as airflow and temperature).

[0232] The stress-strain curves of x-PBB-SEBS with different crosslinking degrees were measured. Fig.11 ). The results show that as the degree of crosslinking increases, the tensile strength and Young's modulus increase as follows: 30x-PBB-SEBS: 20.2MPa and 360.3MPa <40x-PBB-SEBS: 25.1MPa and 485.6MPa <50x-PBB-SEBS: 27.3MPa and 650.4MPa. In contrast, as the degree of crosslinking increases, its elongation at break decreases as follows: 30x-PBB-SEBS: 75.1% > 40x-PBB-SEBS: 70.3% > 50x-PBB-SEBS: 59.4%. As the degree of crosslinking increases, the content of the elastic polymer SEBS decreases; therefore, the bonds between poly(bibenzyl N-methylpiperidinium) and bromohexyl SEBS increase, making the polymer chains more tightly bonded together.

[0233] Then, the mechanical properties of x-PBB-SEBS membranes were compared with those of SEBS-based AEMs (

[31] J. Polym. Sci. 58 (2020) 2181–2196;

[33] J. Membr. Sci. 599 (2020), 117829;

[34] Int. J. Hydrogen Energy 45 (2020) 15658–15671;

[35] J. Membr. Sci. (2022), 120029), polyphenylene-based AEMs ([9] J. Power Sources 487(2021),229429;

[10] J.Mater.Chem.A.Mater.9(2021)327–337;

[11] Nat.Commun.12(2021)2367;

[12] J.Membr.Sci.621(2021);

[47] J.Membr.Sci.638(2021),119685;

[53] J.Membr.Sci.647(2022),120341;

[54] Angew.Chem.133(2021)7789–7797), and xTQA-PPO-SEBS AEM prepared by crosslinking PPO and SEBS (

[48] Korean Patent No. 10-2184530) were compared (Table 2).

[0234]

Table 2

[0235]

[0236] The results showed that the x-PBB-SEBS-based membranes were between SEBS-based AEMs and polyphenylene-based AEMs in terms of tensile strength and elongation at break. It was confirmed that the x-PBB-SEBS membranes were made by cross-linking these two polymers of different properties, so they exhibited mechanical stability, such as excellent tensile strength and Young's modulus and high elongation at break. In addition, their mechanical properties could be controlled by adjusting the degree of cross-linking.

[0237] The elongation at break and Young's modulus of x-PBB-SEBS were compared with those of AEMs reported in previous studies (

[11] Nat. Commun. 12 (2021) 2367;

[12] J. Membr. Sci. 621 (2021);

[31] J. Polym. Sci. 58 (2020) 2181–2196;

[34] Int. J. Hydrogen Energy 45 (2020) 15658–15671;

[35] J. Membr. Sci. (2022), 120029;

[48] Korean Patent No. 10-2184530) Fig.12 ). The results showed that the x-PBB-SEBS films exhibited similar Young's modulus to other AEMs; however, the elongation at break of the x-PBB-SEBS films was higher when the films had similar Young's modulus values. In particular, the x-PBB-SEBS films exhibited better mechanical properties than the xTQA-PPO-SEBS films prepared by crosslinking PPO and SEBS reported in previous studies. This was attributed to the crosslinking of poly(bibenzyl N-methylpiperidine) and SEBS (both of which have excellent phase separation), leading to improved mechanical properties.

[0238] Next, TGA and DSC were used to determine the thermal stability of the x-PBB-SEBS film ( Fig.13 In the TGA curve, the weight loss occurs in three stages ( Fig.13 a). The first weight loss (30-150°C) is attributed to the evaporation of free and bound water contained in the film. As the degree of cross-linking increases, the weight loss decreases because the amount of water contained in the film, i.e., the water uptake (WU), decreases. The second weight loss (150-300°C) is attributed to the degradation of the conductive groups, while the third weight loss (above 400°C) is attributed to the decomposition of the polymer backbone.

[0239] DSC analysis was performed to determine the glass transition temperature (T g In all three x-PBB-SEBS, no obvious peaks were observed at temperatures up to 200 °C, which is the decomposition temperature of QA ( Fig.13 b) Considering the T of SEBS or functionalized SEBS g Typically between 50 and 70 °C, this observation confirms that cross-linking of high-rigidity polymers contributes to improved thermal stability.

[0240] According to these TGA and DSC results, all three x-PBB-SEBS membranes exhibited suitable thermal stability and can be used in the temperature range of 60–80 °C, which corresponds to the typical operating conditions of AEMFCs.

[0241] Experimental Example 3: Water Retention Capacity

[0242] (1) Measurement method

[0243] The frozen water and non-frozen water contents of the films were measured by DSC using a PerkinElmer DSC 4000. A fully hydrated film sample was sealed in an aluminum pan, and a sealed empty aluminum pan was prepared as a reference. Both pans were weighed and frozen to −40 °C in the DSC chamber. Then, the temperature was kept constant while the system was equilibrated. Afterwards, the temperature was adjusted at 2 °C min -1Heat the DSC chamber to 20°C at a heating rate of 1.5 %. Repeat this cycle twice and obtain the value from the second thermal cycle. m ) was integrated to calculate the amount of frozen water in each membrane. The total water content was determined using the WU (%) of the membrane. The frozen water and non-freezing water contents were calculated using the following formula:

[0244] Frozen water (%) = [melting enthalpy (J g -1 )] / [The melting heat of pure water (334 J g -1 )]×100

[0245] Non-frozen water (%) = total water (%) - frozen water (%)

[0246] (2) Results

[0247] AEMs must have a high WU to provide high ionic conductivity and good battery performance. The water contained in the membrane can be divided into free water and bound water. Free water does not actively interact with ion-conducting groups, so its freezing and boiling temperatures are comparable to those of ordinary water. In contrast, bound water interacts strongly with ion-conducting groups and therefore exhibits a lower freezing temperature and a higher boiling temperature than free water. According to previous studies, ensuring a high content of bound water in the membrane is very important for achieving high-performance fuel cells because the free water content in the membrane is unlikely to be high under the actual operating conditions of fuel cells, that is, at high temperatures and 90%-95% RH.

[0248] Then, TGA and DSC were used to analyze the bound water content of x-PBB-SEBS membrane ( Figure 2 In the TGA curve, the weight loss from 30°C to 100°C is classified as free water, and the weight loss from 100°C to the temperature range where the ion-conductive group decomposes is classified as bound water ( Figure 2 a). Given the different WUs of the three x-PBB-SEBS membranes, this analysis has a limitation as it is not a quantitative comparison of bound water but a relative comparison.

[0249] The results showed that the bound water content of the membrane increased with increasing crosslinking degree, as follows: 30x-PBB-SEBS: 19.71% < 40x-PBB-SEBS: 28.34% < 50x-PBB-SEBS: 33.42%. This is attributed to the increased interaction between the ion-conductive groups and water with increasing crosslinking degree. To confirm this explanation, DSC was further used to analyze the freezable water and non-freezable water ( Figure 2 As a result, the freezing temperatures (T F: dotted line) are all below 0°C, the freezing point of water, which indicates that the ion conductive groups interact with water. In addition, with the increase of crosslinking degree, the non-freezing bound water content increases, and the freezing temperature of water (T F ) moves to lower temperatures, as follows: 30x-PBB-SEBS: -2.7°C > 40x-PBB-SEBS: -4.5°C > 50x-PBB-SEBS: -6.8°C. This is due to the increased degree of crosslinking, which leads to enhanced interactions between water and ion-conductive groups, which is also consistent with the trend of bound water content in the TGA results.

[0250]

Table 3

[0251] Free water (%) Bound water (%) Unfrozen bound water (%) 30x-PBB-SEBS 80.29 19.71 77.66 40x-PBB-SEBS 71.66 28.34 85.52 50x-PBB-SEBS 66.58 33.42 92.36

[0252] Experimental Example 4: Morphology and Hydroxide Ion Conductivity

[0253] (1) Morphological analysis

[0254] The morphology of each film was imaged and analyzed using a field emission transmission electron microscope (FE-TEM, Talos F200X, ThermoFisher Scientific, MA, USA) at an accelerating voltage of 200 kV. The sample was prepared as follows: 3-4 drops of 1 wt% polymer in CHCl3 solution were placed on a copper grid to make a homogeneous film. The grid was dried at 40 °C for 12 hours and then treated with TMA solution at 45 °C for 12 hours. After TMA treatment, the grid was rinsed with deionized water to remove excess TMA and dried in an oven at 40 °C.

[0255] The microphase separation of the films was observed using an atomic force microscope (AFM, Bruker MULTIMODE-8-AM, Billerica, MA, USA).

[0256] (2) Hydroxide ion conductivity

[0257] The hydroxide ion conductivity (σ) of each membrane was measured by double probe impedance spectroscopy using an AC impedance analyzer (SP-200, Bio-Logic SAS, Claix, France). The electrode system was connected at a frequency of 100 mHz to 2 MHz. Rectangular samples with a size of 1×4 cm were prepared. The hydroxide ion conductivity was measured using resistance (R) in deionized water at 20°C to 80°C. The hydroxide ion conductivity was calculated using the following formula:

[0258] σ=L / (R×A)

[0259] where L is the distance between the reference electrodes and A is the cross-sectional area of ​​the membrane.

[0260] (3) Results

[0261] The ionic conductivity of AEM is one of the most important factors that directly affect battery performance. Therefore, the hydroxide ion conductivity of x-PBB-SEBS membranes with different crosslinking degrees was measured in water at 20-80°C. In addition, the normalized conductivity was calculated by dividing the hydroxide ion conductivity by the IEC to compare the overall ionic conduction efficiency of each membrane ( Figure 3 a and Table 4).

[0262] As a result, the hydroxide ion conductivity and normalized conductivity of 40x-PBB-SEBS were the highest, ranging from 72.28 to 146.25 mS cm -1 and 38.45-77.79mS cm -1 Since the IEC in AEM is related to the number of ion-conducting groups, membranes with high IEC generally have high conductivity. -1 ) showed a higher crosslinking degree than 30x-PBB-SEBS (1.97 meq g -1 ) higher ionic conductivity, which may be due to the increased interaction between the ion-conductive groups and water in the membrane with a cross-linking degree of 40%, resulting in an increase in the bound water content. At the same time, according to the above TGA and DSC measurement results, 50x-PBB-SEBS exhibited a higher bound water content than 40x-PBB-SEBS. This means that the ionic conductivity of the x-PBB-SEBS membrane is affected by factors other than water retention capacity.

[0263] In addition, the RH conductivity ( Figure 3 b and Table 4). From the measurement results, it can be confirmed that the behavior of ionic conductivity under fuel cell operating conditions is more closely related to the normalized conductivity, i.e., the ionic conduction efficiency, than to the conductivity in water.

[0264]

Table 4

[0265]

[0266] a Measured at 60°C and 95% RH

[0267] Subsequently, the morphology of xPBB-SEBS membranes with different crosslinking degrees was analyzed. In the AFM images, hydrophilic-hydrophobic phase separation was clearly observed in all three membranes ( Figure 4 a-4c). Especially in 40x-PBB-SEBS, this phase separation becomes more obvious.

[0268] Furthermore, the normalized conductivity of the x-PBB-SEBS membrane was compared with that of SEBS-based AEMs, polyphenylene-based AEMs known to have excellent ionic conductivity according to recent reports, and cross-linked xTri-PPO-SEBS membranes ([7] Nat. Energy 4 (2019) 392–398;

[10] J. Mater. Chem. A. Mater. 9 (2021) 327–337;

[11] Nat. Commun. 12 (2021) 2367;

[31] J. Polym. Sci. 58 (2020) 2181–2196;

[32] Int. J. Hydrogen Energy 46(2021)36301–36313;

[35] J. Membr. Sci. (2022), 120029;

[41] J. Mater. Chem. A. 7(2019) 6883–6893;

[53] J. Membr. Sci. 647(2022), 120341;

[54] Angew. Chem. 133(2021) 7789–7797) were compared ( Fig.14 All three x-PBB-SEBS membranes exhibited high normalized conductivity, although their IECs were relatively low (<2.0 meq g -1 ).

[0269] This result is attributed to the introduction of SEBS polymers that enhance the WU of the x-PBB-SEBS membrane, coupled with the cross-linking effect that ensures that the WU does not increase excessively. In this way, the membrane has a WU suitable for efficient ion conduction, resulting in high ion conduction efficiency. In addition, the cross-linking of the two polymers with excellent phase separation facilitates the formation of ion channels, further improving the ion conduction efficiency. Notably, the 40x-PBB-SEBS membrane has one of the highest normalized conductivities (38.45 mS cm) compared to other AEMs reported in previous studies. -1 This is attributed to the high water retention capacity of the membrane supported by excellent phase separation, as confirmed by the TGA and DSC results above.

[0270] Experimental Example 5: Alkaline Stability

[0271] (1) Measurement method

[0272] OH -The membranes of the form were immersed in a 2M KOH solution at 80°C for 720 hours to evaluate their chemical stability by measuring the changes in IEC and conductivity. Before the measurement, each membrane was immersed in a freshly prepared 1M KOH solution at 60°C for at least 24 hours. Thereafter, the hydroxide ion conductivity of each membrane was measured in deionized water at 20°C (at intervals of 120 hours), and the IEC was measured by back titration before and after each alkaline stability test, as described above.

[0273] (2) Results

[0274] The alkaline stability test results are as follows Figure 5 In all x-PBB-SEBS membranes with different crosslinking degrees, the conductivity retention was still above 99% even after 720 h ( Figure 5 a). It was also found that the IEC of all three membranes remained almost unchanged after 720 hours ( Figure 5 b).

[0275] The excellent alkaline stability of the x-PBB-SEBS membrane is attributed to the introduction of a polymer backbone without aryl ethers, which effectively inhibits the decomposition of the polymer chains. This inhibition, coupled with the cross-linking effect, helps to enhance the chemical stability of the polymer chains and ion-conducting groups. The excellent phase separation of the polymer also enhances the chemical stability of the membrane.

[0276] At the same time, the alkaline stability of the x-PBB-SEBS membranes of Examples 1 to 3 was compared with that of SEBS-based AEMs (

[34] Int. J. Hydrogen Energy 45 (2020) 15658–15671;

[35] J. Membr. Sci. (2022), 120029) and polyphenylene-based AEMs without aryl ethers known to have excellent alkaline stability ([7] Nat. Energy 4(2019)392–398;

[10] J.Mater.Chem.A.Mater.9(2021)327–337;

[11] Nat.Commun.12(2021)236 7;

[13] J.Membr.Sci.642(2022),119966;

[41] J.Mater.Chem.A.7(2019)6883–6893;

[42] Energy Environ.Sci.13(2020)3633–3645;

[45] Int.J.Hydrogen Energy 46(2021)18524–18533;

[47] J.Membr.Sci.638(2021),119685;

[53] J.Membr.Sci.647(2022),120341;

[54] Angew.Chem.133(2021)7789–7797;

[58] Membranes 10(2020)1–16), and the xTQA-PPO-SEBS membrane developed in a previous study (

[48] Korean Patent No. 10-2184530) were compared (Table 5).

[0277]

Table 5

[0278]

[0279]

[0280] a QA = quaternary ammonium, Pip = piperidinium

[0281] The results confirmed that the x-PBB-SEBS membrane exhibited excellent alkaline stability comparable to that of the reported AEMs with excellent alkaline stability.

[0282] Experimental Example 6: Oxidative Stability

[0283] (1) Fenton test

[0284] The membrane was immersed in Fenton solution (3 wt % H2O2 containing 4 ppm Fe) at room temperature (25 °C) at intervals of 24 h. 2+) for 120 hours. Thereafter, each membrane was washed several times with distilled water to remove the Fenton solution and then dried in an oven at 40°C for at least 24 hours. The oxidative stability of the membrane was evaluated based on the changes in the weight and thermal stability of the membrane.

[0285] As a result, all three films, 30x-PBB-SEBS, 40x-PBB-SEBS, and 50x-PBB-SEBS, showed excellent oxidative stability with a weight loss of less than 1% and maintained their shape after the test.

[0286] (2) TGA analysis

[0287] TGA patterns were analyzed before and after the oxidation stability test to examine the structural changes of 40x-PBB-SEBS ( Fig.15 ). After drying each film in a 40°C oven for 12 hours or more, TGA analysis was performed. As a result, 40x-PBB-SEBS showed similar TGA graphs before and after the oxidation stability test, indicating that its initial polymer structure remained unchanged during the test.

[0288] Experimental Example 7: Fabrication of a membrane electrode assembly (MEA) and single cell measurement

[0289] (1) Measurement method

[0290] For single cell measurements, the membranes were pretreated with 1 M KOH for 24 h and rinsed with deionized water. The catalyst ink was prepared using ultrasonic treatment with Pt / C catalyst (Pt / C, 40 wt %, Alfa Aesar, Haverhill, MA, USA), 1-propanol, and ionomer (FAA-3-SOLUT-10, Fumatech, Germany). Pt was loaded onto the anode and cathode with a coverage of 0.4 mg cm -2 . Then, the catalyst ink was applied to the prepared membrane surface using an air spray gun. The catalyst-coated membrane was immersed in a 1 M KOH solution for 12 h and washed with deionized water. The MEA (membrane electrode assembly) was sandwiched between a gas diffusion layer (SIGRACET39BB) and a gasket, and the active area of ​​the unit cell was 5 cm 2 For the single cell performance test, H2 / O2 were added at 200 and 400 mL min -1 The battery temperature was 60°C, the relative humidity was 100% or 70%, and the activation process was performed by repeating the load cycle (0.6, 0.4 V) for 2 hours before the single cell performance test.

[0291] (2) Results

[0292] Single cell tests were performed using x-PBB-SEBS membrane at 60°C and 100% RH ( Figure 6 a). It was found that the performance of the single cell was improved as follows: 30x-PBB-SEBS (504 mW cm -2 and 657mA cm -2 @0.6V)<50x-PBB-SEBS(529mWcm -2 and 677 mA cm -2 @0.6V)<40x-PBB-SEBS(555mW cm -2 and 665mA cm -2 @0.6V). This pattern is consistent with what is observed in RH conductivity measurements rather than the conductivity measured in water. This confirms that the cell performance of AEM is more dependent on the conductivity under RH conditions rather than in water, which is also consistent with the results of previous studies.

[0293] Subsequently, the single cell performance was measured after changing the humidification conditions of the x-PBB-SEBS membrane. During AEMFC operation, water is consumed at the cathode and produced at the anode. Therefore, flooding may occur when the anode is under high RH conditions. Therefore, single cell measurements were performed under anode / cathode RH conditions set to 70% / 100%, and each single cell performance was compared with the anode / cathode 100% / 100% RH conditions ( Figure 6 b and Fig.16 The single cell performances of the three x-PBB-SEBS films showed similar trends to those measured under 100% / 100% RH conditions, as follows: 30x-PBB-SEBS (461 mW cm -2 and 625mA cm -2 @0.6V)<50x-PBB_SEBS(503mW cm -2 and 665mA cm -2 @0.6V)<40x-PBB-SEBS(545mW cm -2 and 665mA cm -2 @0.6V). In addition, the peak power density of 30x, 40x, and 50x-PBB-SEBS remained at 91.5%, 98.2%, and 95.1%, respectively, depending on the RH condition. This result was attributed to the increase in water retention capacity and morphological changes with increasing crosslinking degree.

[0294] in conclusion

[0295] In the cross-linked copolymer according to one embodiment of the present invention, the first chain and the second chain showing phase separation are cross-linked to show an excellent phase separation effect, thereby showing high strain characteristics (high elongation at break) and excellent Young's modulus. Therefore, it is confirmed that the cross-linked copolymer of the present invention has excellent mechanical properties by simultaneously satisfying the high stress of the PP-based polymer film and the high strain of the SEBS-based polymer film.

[0296] The cross-linked copolymer exhibits excellent water retention capacity, i.e., strong interaction between the ion-conductive groups and water. In addition, the AFM and TEM analysis results confirm that the cross-linked copolymer has excellent phase separation, i.e., optimal morphology, and therefore, excellent normalized conductivity, an indicator of ion conduction efficiency.

[0297] In addition, the cross-linked copolymer exhibits excellent alkaline stability (more than 99% in 2M KOH at 80°C), which is attributed to the cross-linking of the first chain and the second chain, both of which have no aryl ether structure. In addition, due to excellent phase separation, it exhibits excellent oxidative stability. In addition, when the cross-linked copolymer is used as an anion exchange membrane of a fuel cell, the current density is excellent.

[0298] From the above results, it can be confirmed that the cross-linked copolymer of the present invention shows excellent electrochemical properties and mechanical properties, and physical properties can be controlled by adjusting the degree of cross-linking. Therefore, it can be seen that the cross-linked copolymer can be appropriately used as an anion exchange membrane material that can improve the performance and stability of fuel cells, etc.

Claims

1. A cross-linked copolymer comprising a first chain represented by the following Chemical Formula 1 and a second chain represented by the following Chemical Formula 2, wherein the first chain and the second chain are cross-linked with each other: [Chemical formula 1] In Chemical Formula 1, * is the bonding position with Chemical Formula 2, The sum of q1, q2, q5 and q6 is an integer from 100 to 1000, The sum of q3 and q4 is an integer from 150 to 2000, a and b are each independently an integer from 3 to 10, and R1 to R4 are each independently hydrogen or -(CH2) p -CH3, wherein p is an integer from 0 to 5, [Chemical formula 2] In chemical formula 2, * is the bonding position with Chemical Formula 1, x and y are each independently an integer from 0 to 10, and n is 10 to 1000.

2. The cross-linked copolymer according to claim 1, in, Based on 100 moles of the first chain, 10 to 70 moles of the second chain are included.

3. The cross-linked copolymer according to claim 1, in, q1 to q6 are each independently an integer of 10 to 500.

4. The cross-linked copolymer according to claim 1, in, The ratio of the sum of q1, q2, q5 and q6 to the sum of q1 to q6 is 0.2 to 0.

5.

5. The cross-linked copolymer according to claim 1, in, The ratio of the sum of q1 and q6 to the sum of q1, q2, q5 and q6 is 0.2 to 0.

5.

6. The cross-linked copolymer according to claim 1, in, a and b are each independently an integer of 4 to 6.

7. The cross-linked copolymer according to claim 1, in, The cross-linked copolymer is represented by the following chemical formula 3: [Chemical formula 3] In Chemical Formula 3, q1 to q6, a, b, x, y and n are as defined in Chemical Formulas 1 and 2.

8. A polymer film comprising the cross-linked copolymer according to any one of claims 1 to 7.

9. The polymer film according to claim 8, in, The polymer membrane is an anion exchange membrane.

10. A method for preparing a cross-linked copolymer, comprising the following steps: (a) preparing a polymer represented by the following chemical formula 1-1; (b) preparing a polymer represented by the following Chemical Formula 2-1; and (c) preparing a cross-linked copolymer by cross-linking a polymer represented by the following Chemical Formula 1-1 and a polymer represented by the following Chemical Formula 2-1: [Chemical formula 1-1] In Chemical Formula 1-1, The sum of q1, q2, q5 and q6 is an integer from 100 to 1000, The sum of q3 and q4 is an integer from 150 to 2000, a and b are each independently an integer from 3 to 10, R1 to R4 are each independently hydrogen or -(CH2) p -CH3, wherein p is an integer from 0 to 5, and X1 and X2 are each independently a halogen group, [Chemical formula 2-1] In chemical formula 2-1, x and y are each independently an integer from 0 to 10, and n is 10 to 1000.

11. The method for preparing a cross-linked copolymer according to claim 10, The method further comprises the step (d): reacting the cross-linked copolymer with trimethylamine.

12. The method for preparing a cross-linked copolymer according to claim 10, in, The polymer represented by Chemical Formula 1-1 contains 30 to 90 moles of the halogen group based on 100 moles of the styrene repeating unit.

13. The method for preparing a cross-linked copolymer according to claim 10, in, In the step (c), the polymer represented by Chemical Formula 2-1 is used in an amount of 10 to 70 moles based on 100 moles of the halogen groups contained in the polymer represented by Chemical Formula 1-1.